Development and sustainability of industrial waste-based red mud hybrid composites. (1st September 2019) - Vigneshwaran, S.; Uthayakumar, M.; Arumugaprabu, V.
Abstract: The increasing production of red mud waste is a major threat to the environment as red mud is difficult to manage and causes serious environmental issues. Red mud wastes are rich in mineral content and the addition of such wastes as fillers in polymer composites can improve the mechanical performance. In view of this, a hybrid composite is fabricated using red mud as a filler and sisal fibre as the reinforcement in a polyester matrix. The impact of the addition of red mud on the hybrid composite density, void, tensile strength, impact strength, hardness, and water absorption behaviour was investigated. The mechanical properties of the developed hybrid composites were enhanced considerably when compared to unfilled sisal/polyester composites. The hybrid composites showed a reduction in water intake percentage; however, increasing the red mud weight percentage showed an increase in the water intake percentage. In both the mechanical and water absorption tests, an increase in the red mud percentage indicated a negative impact. Red mud percentages of 10% and 20% demonstrated good bonding with the fibre and the matrix; this was evident from the scanning electron microscopy images. The fabricated red mud filled composites were demonstrated to be a sustainable and economical solution for red mud waste management. Graphical abstract: Image 1 Highlights: A cleaner production approach by effective use of red mud industrial waste. Red mud waste is used as filler in hybrid composite fabrication. Red mud filler improved the mechanical strength and reduced water absorption. Composite with 20% red mud exhibits superior mechanical characteristics.